Collective Immunity to Virus Measles of Medical Workers and Students of Medical Colleges in the Republic of Tatarstan - L. G. Avdonina; M. A. Patyashina; G. Sh. Isaeva; I. D. Reshetnikova; Yu. A. Tyurin; S. N. Kulikov; L. R. Yuzlibaeva; G. F. Gilyazutdinova; N. Hakimov (Эпидемиология и вакцинопрофилактика, 2019)
Relevance. Within the framework of the state assignment in the, Kazan Scientific Research Institute of Epidemiology and Microbiology together with the Department of Rospotrebnadzor in the Republic of Tatarstan, the analysis of the tensions of collective immunity to measles in at-risk groups among medical workers, students of medical colleges in Kazan, Naberezhnye Chelny, Buinsk and Muslyumovsky districts for the period 2015‒2017.Materials and methods. Immunoenzyme method of analysis studied the intensity of immunity against measles in 1107 serum samples of medical workers from 19 medical and preventive institutions in cities and some regions of the Republic of Tatarstan, and students of medical schools and colleges.Results. It was established that out of 480 medical personnel, 363 (75,63 ± 2,253%) were seropositive to the measles virus, and 117 (24.38 ± 3.969%) were seronegative. Coverage by vaccination and revaccination against measles among the sample group of medical workers did not reach the level of 93% (84.38 ± 1.657%), which does not prevent the outbreak of measles among this group. According to the results of a sample survey of antibodies to measles virus among students of medical schools and colleges of the Republic of Tatarstan (data for 2016 and 2017), it was found that the proportion of seronegative measles virus among students in large cities of the Republic of Tatarstan in 2016 was 52.35 ± 2,99%, and in 2017, 42.32 ± 2.958% of the people. The proportion of students who were seronegative for measles virus for two years of the study (2016–2017) averaged 45.07 ± 2.979%.Discussion and conclusions. The results indicate the need to continue conducting studies on seromonitoring of collective immunity to measles in medical workers, students in secondary and higher medical schools.